Fermionic steering in multi-event horizon spacetime - Shu-Min Wu; Jin-Xuan Li; Yu-Xuan Wang; Si-Han Shang; Jianbo Lu (European Physical Journal C: Particles and Fields)
Abstract We investigate quantum steering of Dirac field for different types of Bell states in Schwarzschild–de Sitter (SdS) spacetime that has a black hole event horizon (BEH) and a cosmological event horizon (CEH). We find that fermionic steerability from Bob to Alice is greater than fermionic steerability from Alice to Bob, while bosonic steerability exhibits the opposite behavior in SdS spacetime. These different properties between fermionic and bosonic steering arise from the differences between Fermi–Dirac statistics and Bose–Einstein statistics. We also find that the Hawking effect of the black hole decreases fermionic steerability. However, the Hawking effect of the expanding universe can enhance fermionic steerability, which differs from the properties of quantum steering in single-event horizon spacetime. Interestingly, we can indirectly protect quantum steering by using appropriate types of Bell states in multi-event horizon spacetime. These conclusions are helpful to guide the task of processing relativistic quantum information for quantum steering in SdS spacetime.